Framing Mass Hysteria Covid-19 dalam Berita Tempo dan Detikx - Khairul Arief Rahman; Hamidah Izzatu Laily (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
Coverage of the Coronavirus or Covid-19 in Indonesia was accompanied by confusion of information which resulted Mass Hysteria. Media criticism is also present as the vanguard of social control, which is not only limited to what and how it appeared, but also critically explores readiness from the political level of government to the social life of the affected community. How two "premium" media, namely Tempo and DetikX, build news construction about Covid-19? Then how do the media frame a topic or issue that has developed after Covid-19? and how is the concentration of the media in reporting on Mass Hysteria that developed after Covid-19 in Indonesia? This study takes news in March 2020, Especially on the main coverage presented by both media. This research uses qualitative research method and Pan and Kosicki's framing analysis model for explore data research. The Result is Tempo Magazine and DetikX generally drawing struggle toward Mass Hysteria and affair caused by Covid-19 on critics of handling policy government level and public with selectively choosing solution frame as shape of struggle.